Together in mission : the Anglican Church in Malawi and the Church of England Birmingham, 1966-2016 - Tucker, Richard (Priest); Tengatenga, James (Mzuni Press, 2022)
The Malawi Birmingham Partnership dating back to 1966 was one of the earliest'companion links'between an English and an overseas diocese and has been one of the most dynamic. With the help of a chapter by Professor James Tengatenga, a distinguished scholar of global Anglicanism and former Bishop of Southern Malawi, Richard Tucker traces the partnership's origins in the church histories of Malawi and Birmingham. He recounts its development as it has responded to the splitting of one diocese in Malawi into four, the Africanisation of the church leadership, and challenges including the final stages of the Banda dictatorship, famine and the AIDS pandemic, alongside growing secularisation in the UK.